2009
DOI: 10.1119/1.3225922
|View full text |Cite
|
Sign up to set email alerts
|

The longitude problem from the 1700s to today: An international and general education physics course

Abstract: For instructors wishing to use physics as part of an international or general education course, the framework for a course based on the "longitude problem" from the 1700s is described. The longitude problem is teeming with basic principles of physics and astronomy, which makes it ideal for a nonscience-major-based college-level course. This paper summarizes the longitude problem in the context of conceptual physics and astronomy and outlines an appropriate curriculum. Specifics on teaching such a course in Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Jefferson explained that he came to this invention thanks to his efforts to find a simple method to determine the longitude of Monticello. At that time, the longitude problem, both at land and at sea, was a challenging problem worldwide, as was well described by Bensky (2010). Bensky also proposed a longitude-based international and general education physics course.…”
Section: Mapping Of the Earth's Daily Rotation Onto A Dingmentioning
confidence: 97%
“…Jefferson explained that he came to this invention thanks to his efforts to find a simple method to determine the longitude of Monticello. At that time, the longitude problem, both at land and at sea, was a challenging problem worldwide, as was well described by Bensky (2010). Bensky also proposed a longitude-based international and general education physics course.…”
Section: Mapping Of the Earth's Daily Rotation Onto A Dingmentioning
confidence: 97%
“…It has been shown that general studies courses can be quite effective in increasing science literacy [1,2]. This paper describes a laboratory based, general education course, developed by the Physics Program at Stockton University.…”
Section: Introductionmentioning
confidence: 99%
“…The Google Earth program (previously discussed in this journal [1][2][3][4] and elsewhere [5]) and the related database accessed via web browser, Google Maps, provides high resolution aerial imagery of the Earth, which can be used to investigate multiple physical phenomena of interest. While most of the activities we discuss could be performed locally without aerial imagery, the software and website allow students to explore clear-cut examples of the concepts mentioned without the need to travel or to avoid inclement weather or darkness.…”
Section: Introductionmentioning
confidence: 99%